Selection and validation of reference genes for normalizing qRT‒PCR gene expression studies in Colletotrichum gloeosporioides and interaction with the guava plants - Haq, Imran Ul; Ijaz, Siddra; Hashem, Abeer; Avila-Quezada, Graciela Dolores; Abd_Allah, Elsayed Fathi (Frontiers in Plant Science, 2023)
Quantitative real-time PCR is used to quantify gene expression, even to detect low-level transcripts. It detects and quantifies the inoculum level of fungal pathogens in infected hosts.However, reliable expression profiling data require accurate transcript normalization against a stable reference gene. Hence, using stably expressed reference genes under variable conditions is paramount in gene expression analysis. In the current study, reference genes were selected and validated in Colletotrichum gloeosporoides, a guava canker and dieback pathogen. The reference gene selection and validation in C. gloeosporoides were evaluated for germinated conidia and mycelium (in vitro) and in infected guava (Psidium guajava) (interaction with host plant). The CgCAL gene was determined as a highly stable reference gene, followed by the CgTUB2 in C. gloeosporoides for germinating conidia and mycelium. However, the CgTUB2 gene was determined to be a highly stable reference gene, followed by the CgCAL for expression analysis during its interaction with the plant. Expression profiling revealed stable and constant relative expression patterns of selected reference genes for both PR genes by determining their relative transcript level. This study is the first to describe reference gene selection and validation to quantify target gene expression in C. gloeosporoides.